PEMBELAJARAN MATEMATIKA DENGAN MODEL MISSOURI MATHEMATICS PROJECTUNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP - Sigit Setyawan Putra; Harina Fitriyani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This research was conducted because of the low ability of students to solve mathematical problems. The purpose of this research is to improve students’ problem solving ability of math grade VII semester II of SMPN 9 Yogyakarta in academic year 2016/2017 by using learning model of missouri mathematics project (MMP).This research includes classroom action research which consists of two cycles where each cycle consists of two meetings. Data collection techniques used observation, interviews, and tests. Data analysis was done with a qualitative descriptive analysis.The result of the study shows that learning mathematics using learning model of missouri mathematics project (MMP) can improve the students’ problem solving ability of grade VII of second Semester of SMPN 9 Yogyakarta. The result of analysis from observation sheets in the first cycle in mean percentage of problem solving ability of mathematics included in enough criterion (56,06%), and in the second cycle in good criterion (72,98%). While the results of the analysis of the test scores on the first cycle average percentage of math problem solving skills included in the criteria enough (48.61%), and in the second cycle average percentage of problem solving ability of mathematics included in good criteria (72.06%). Keywords : Improvement, Missouri Mathematics Project, Mathematics Problem Solving Ability